An Analysis of Various Factors Affecting Income Smoothing - Dinda Nur Oktiviasari (Pusat P2M Politeknik Negeri Batam, 2020)
Income smoothing is a part of income management strategy to produce income in a company with normal fluctuation. The freedom a company has to choosing its accounting method and regulations often becomes an opportunity for manager to commit self-interest actions. A company with normal income fluctuations will give it good reputation. So this phenomenon drives it to do income smoothing. The purpose of this research is to find the factors that can affect income smoothing practice in transportation companies listed on Indonesia Stock Exchange 2016-2018. This research uses quantitative method and sample its data with purposive sampling. The data research is secondary data collected from official website of Indonesia Stock Exchange. The analysis techniques uses logistic regression SPSS.23.0. based on the result of this research, variables of managerial ownership, company size, and leverage simultaneously and significantly affect income smoothing with the value of 21,3%. Partially, managerial ownership significantly affect income smoothing with positive direction towards income smoothing, while firm size and leverage don’t affect income smoothing.